REPRESENTATION OF KIM JONG-UN’S SUCCESSION IN BBC NEWS: A CRITICAL DISCOURSE ANALYSIS - Hendra Nugraha (JURNAL ARBITRER, 2016)
This research attempts to reveal representation of Kim Jong-Un’s succession in BBC News through textual and discursive practice analysis. The data of this thesis are taken from BBC News website on 29 and 31 December 2011. The theory applied to seek the objective of the research is Critical Discourse Analysis developed by Fairclough. Through textual and discursive practice analysis, the writer finds pthat BBC employs more passive material clauses than active material clauses in depicting Kim Jong-Un’s succession. BBC also represents Kim Jong-Un’s succession as premature process where Kim Jong-Un is portrayed as a young and inexperienced leader. Besides the prematurity of the succession, the present writer finds that BBC represents Kim Jong-Un’s succession as continuity of Kim’s family dynasty. Thus, the succession is based on his resemblance to Kim Il-Sung, the founder of Democratic People’s Republic of Korea, rather than Kim Jong-Un ability and competency.